Design for the Damping of a Railway Collector Based on the Application of Shape Memory Alloys. (30th December 2012) - Bocciolone, M.; Carnevale, M.; Collina, A.; Lecis, N.; Lo Conte, A.; Previtali, B.; Biffi, C. A.; Bassani, P.; Tuissi, A.
Abstract : A new design of a Cu based SMA/GFRP lateral horn of a railway collector is proposed. Synergistic contribution of the performance parameters associated with the SMA, including specific damping, specific stiffness, and volume fraction, as well as those associated with the host composite such as flexural rigidity, SMA through-the-thickness location, and SMA-host interfacial strength, is taken into account. The aim is to increase the structural damping of the first flexural mode of the horn without significantly changing its flexural stiffness and weight. The focus of this work also applies to manufacturability and the cost effectiveness of the component for future industrial production.